New combinations and typifications in Cryptangieae (Cyperaceae) - Vitta, Fabio A.; Costa, Suzana M.; Amaral, Maria Do Carmo E.; Shepherd, George J.; Thomas, W. Wayt (Phytotaxa, 2021)
New combinations for Cryptangium verticillatum and for Lagenocarpus tristis are proposed here. Three neotypes and three lectotypes for names actually belonging to the genus Cryptangium, and seven lectotypes for names belonging to Lagenocarpus are designated here.